The Effects of GABA-Rich Adzuki Beans on Glycolipid Metabolism, as Well as Intestinal Flora, in Type 2 Diabetic Mice - Zhang, Aiwu; Jiang, Xiujie; Ge, Yunfei; Xu, Qingpeng; Li, Zhijiang; Tang, Huacheng; Cao, Dongmei; Zhang, Dongjie (Frontiers in Nutrition, 2022)
In this study, the effects of γ-aminobutyric acid (GABA)-rich sprouted adzuki beans on glycolipid metabolism and gastrointestinal health were investigated in mice with type 2 diabetes mellitus (T2DM). Mice with T2DM were subjected to dietary intervention with different doses of GABA-rich sprouted adzuki beans for 6 consecutive weeks, during which growth indicators, glycolipid metabolism, and the composition and diversity of the gut microbiota changes were observed. A high dietary intake of GABA-rich sprouted adzuki beans had a preventive effect against weight gain, significantly reduced serum levels of FBG, TG, and TC. Additionally, high dietary intake of GABA-rich sprouted adzuki beans increased the abundances of Firmicutes, Bacteroidetes, Verrucomicrobia, and Akkermansia, leading to a shift in the structure of the gut microbiota towards the dominance of probiotics with regulatory effects on glycolipid metabolism. Our results confirmed that changes in the microbiota may mediate the anti-diabetic effect of sprouted adzuki beans.